Mempertahankan Loyalitas Penikmat Kopi melalui Trust, Satisfaction, Value, Happiness dan Brand Image: (Studi Empirik Pelanggan Starbucks di masa Pandemi Covid-19) - Fajar Nur Feriyanto; Vita Briliana (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2022)
The purpose of this study was to determine and analyze the effect of trust, satisfaction, value, happiness and brand image on loyalty to Starbucks customers in Jakarta. This research design uses descriptive and causal research, using a Likert scale that uses five points in its measurement. The method of determining the sample using purposive sampling method with primary and secondary data. The sample used as many as 110 respondents and data analysis using multiple linear regression with IBM SPSS statistics 25 as a test tool. The results obtained in this study that trust, satisfaction, value and happiness have an effect on loyalty to Starbucks customers in Jakarta, but brand image has no effect on loyalty.